Answer:
C.
Explanation:
We are given
are odd which means:
![f(-x)=-f(x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/87z7jfhaz3al3h1hjkj8z66meronepiia5.png)
![g(-x)=-g(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/fbjf8gzvk73ot6c3gw91v1khq9qnp5x4tw.png)
We can tell if a function,
, is even if
.
We can tell if a function,
, is odd if
.
So let's test your I,II,III.
We will be replacing x with -x to find out.
I.
![p(x)=f(g(x))](https://img.qammunity.org/2020/formulas/mathematics/high-school/a29w1txx3i50fwx8f9xss9bb8v5fwwspa6.png)
![p(-x)=f(g(-x))](https://img.qammunity.org/2020/formulas/mathematics/high-school/lumrqivud3c9ra9jzxggostyzlf6mtmmvb.png)
![p(-x)=f(-g(x))](https://img.qammunity.org/2020/formulas/mathematics/high-school/3upasf953yp3nfbkv8h53hrmzl6oyatjg5.png)
![p(-x)=-f(g(x))](https://img.qammunity.org/2020/formulas/mathematics/high-school/5b0xqtnx29a9j9gybl2f21pbnx0ift26dh.png)
![p(-x)=-p(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/m4k5tyit2xggqpo8ou8oabsgydue3qnhxu.png)
So
is odd.
II
![r(x)=f(x)+g(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/gmzlb8ssrswoy8tdvd48bgxt654a1fv870.png)
![r(-x)=f(-x)+g(-x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/o5ayvzyymel1fx6syjb1z07nk85tcyzwzs.png)
![r(-x)=-f(x)+-g(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/e122npizy38sz0teavlbn6l7xsavettw6i.png)
![r(-x)=-(f(x)+g(x))](https://img.qammunity.org/2020/formulas/mathematics/high-school/3hrxv057yjy7ny801dag0om1n1m3n3hb51.png)
![r(-x)=-(r(x))](https://img.qammunity.org/2020/formulas/mathematics/high-school/9xyt29999tvpe5msuuixc93xbod6lwd88d.png)
![r(-x)=-r(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/z2fcafmecfh12y6u0xxcvqvkca2eaqr043.png)
So
is odd.
III
![s(x)=f(x)\cdot g(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/5alpw3h6n9t0r4lglvg5qmqpzhjoxw7txo.png)
![s(-x)=f(-x) \cdot g(-x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/l0yubq48at54lzoy234eqzo4g0pteni2kg.png)
![s(-x)=-f(x) \cdot -g(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/c8uwrnnc9iddkffqofj1wtagqr71lk4z6a.png)
![s(-x)=f(x) \cdot g(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/dea38hs9184xti26c54dj0vo0tnwfczein.png)
![s(-x)=s(x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/iy04ftc0vnzl0cnazhu42b74t8fzx75ofs.png)
So
is even.
So I and II are odd and III is even.
C. is the answer.